Superpropos: Product Ordering System - Rina, Ishak (2023)
The growing interest in e-commerce has made the internet the primary platform for conducting business. However, in some cases, sellers face challenges when handling large orders from customers. Sellers often need to contact the admin to confirm payments before forwarding orders to the warehouse staff, leading to delays and impacting customer trust. Mistakes in product packaging and delivery also occur due to the similarity of order details. Additionally, sellers struggle to make complaints and ensure accurate order packing. To address these issues, a study of the current method of ordering products in an improvised system was conducted. This study led to the development of the SuperProPOS: Product Ordering System, aimed at streamlining and expediting the order process. After completing the system development, testing was carried out to measure its functionality. The results of the testing showed that the system allows sellers to place orders more efficiently, sending the orders to the admin for approval and subsequently notifying the warehouse staff for packing and updating the order status. Marketers can also monitor seller activities through the system, and sellers can easily lodge complaints regarding any order issues. Overall, this system enhances business process efficiency and customer satisfaction.